Socialization Prevent And Alert Dengue Fever Dengue (DBD) In RT 25 Urban Village Sawah Lebar Sub-District Ratu Agung Kota Bengkulu - Sari, Nofita; Afriani, Tiara; Cahya, Vivina; Yuniarsih, Tri; Gustian, Tedi; Saskia, Vera; Wulandari, Wulandari (Jurnal Pengabdian Mandiri, 2024)
Dengue fever is one of the health problems in Bengkulu City. DHF is one of the diseases that needs to be watched out for because it can cause death and can occur due to a less clean environment. Various efforts have been made to prevent the outbreak of DHF. The approach to eradicating DHF that is based on community awareness is one alternative in order to control the spread of this disease. The purpose of this study is to increase knowledge and awareness about the dangers of Dengue Fever. The method used in the research is through counseling. Results and Discussion in this KKN activity with the title “BDB Counseling in Rt. 25 Sawah Lebar Village, Bengkulu City”. Based on the results of this activity, it is to increase public knowledge about the dangers of dengue fever. The method of this activity is counseling. This activity is considered quite successful, where participants are enthusiastic to ask questions and feedback from participants this counseling is considered interesting, exciting, relevant and useful.Suggestion: As a result of this flood disaster counseling activity, it is hoped that the community will gain knowledge about dengue fever.